Interlinkage between Sustainable Development and Human Rights in States Reports to International Mechanisms - Reis, Saionara; Joana Soler Torramilans; Winterskov, Helene; Jørgensen, Stinne Skriver (Routledge Handbook of the UN Sustainable Development Goals Research and Policy, 2025)
This handbook brings together a collection of seminal research on the Sustainable Development Goals (SDGs) and investigates the effectiveness of the 17 goals for achieving transformative change toward sustainable development. As a collection of inter- and transdisciplinary research from around the world, this volume explores the applications, implications, and best practices of the goals at thematic, regional, and national levels, providing specific examples from a diverse range of places, such as Australia, Brazil, China, DRC, India, Italy, the Sahel region of Africa, and the USA, among others. The book serves as a mid-term evaluation of the SDGs, bringing to the fore comprehensive experiences and evidence related to the SDGs, whilst highlighting the interlinkages between the different goals. The handbook is divided into two parts: Part I brings together groundbreaking research to define, identify, and present conceptual frameworks for a sustainable future, whilst Part II focuses on the policies, practices, and implementation of the SDGs. The chapters identify key aspects missing from the 2030 Agenda, such as global power imbalances, cultural diversity, Indigenous rights, and unsustainable levels of consumption; they also critically evaluate the overall delivery and effectiveness of the SDGs whilst outlining potential future directions for the post-SDG 2030 Agenda. This handbook is aimed at a diverse and global audience of academics and students of economics, business studies, political science, and development studies. It will also serve as a valuable reference for leaders in the industry, the public sector, civil society, and international policymakers keen to gain a better understanding of the SDGs.